Boosting exciton dissociation and charge separation in pyrene-based linear conjugated polymers for efficient photocatalytic hydrogen production. Issue 45 (11th November 2022) - Hao, Lei; Shen, Rongchen; Chen, Shuling; Bi, Weiling; Wang, Lei; Liang, Guijie; Zhang, Peng; Li, Xin
Abstract : The pyrene–fluorenone linear conjugated polymers exhibit the boosted exciton dissociation and charge separation, thus achieving the highest activity for photocatalytic hydrogen evolution. Abstract : Conjugated organic polymers (COPs) have recently attracted intense interest in photocatalytic hydrogen evolution (PHE) due to their easily tuned properties, high stability, and processability. However, most COPs photocatalysts displayed poor PHE performance due to their insufficient light-absorption range and unsatisfactory exciton dissociation and charge separation efficiency. Herein, four novel uniform nanoribbon-like linear COPs were synthesized using fluorenone, fluorene, dibenzothiophene, carbazole, and pyrene by Suzuki–Miyaura reaction. The resultant pyrenefluorenone COP (PyFO) displayed an excellent photocatalytic H2 evolution rate of 43.22 mmol h −1 g −1 under cocatalyst-free conditions. The hydrogen evolution rate could be substantially improved up to 108.4 mmol h −1 g −1 by loading 5% Pt cocatalysts, with the apparent quantum efficiency (AQE) of 35.2% at 420 nm. In particular, the femtosecond time-resolved transient absorption (fs-TA), temperature-dependent PL spectra, UV-vis diffuse reflectance spectroscopy, diverse photo/electrochemical measurements, and theoretical calculations further confirm that the CO as the electron-collecting center in the fluorenone unit structure can enhance the polarization of the electric field within the structure, which facilitates charge separation, migration, and trapping, further inhibits the recombination of electron–hole pairs, and increases the efficiency of exciton dissociation in PyFO, thus achieving the highest activity for photocatalytic hydrogen evolution among the four catalysts. This work provides a promising direction for developing novel pyrene-based linear copolymer photocatalysts.